PEMODELAN SISTEM DINAMIK DAN IMPLEMENTASI SIMULINK PENGENDALIAN KESTABILAN UNMANNED AERIAL VEHICLE MULTIROTOR HEXACOPTER CARGO - Soputra, Steven Wiliam; Tobing, Sheila; Rawikara, Seno Sahisnu (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2023)
The rapid growth of Unmanned Aerial Vehicle (UAV) technology, or drone, has shown its popularity and has been significantly applied to various purposes today. Nevertheless, with all the sophistication of drones, many related topics are still attractive, especially when a drone is designed to carry out a cargo mission. Thus, in this research, the dynamic model of a Hexacopter drone to deliver goods belongs to PT Aero Terra Scan is being developed. This dynamic modeling aims to further the drone's development by modeling it in 2 cases: no-payload and with a payload of 5 kg cases. The dynamic model of this Hexacopter is based on flight dynamics, a field of science studied in Aeronautical Engineering, and is implemented using Simulink. Through the results of this research, several conclusions have been withdrawn: (1) The drone's unstable nature characteristic inherently, even though it is analyzed from the initial hover condition. Thus, the drone and its system as a whole can never be separated with the feedback control that made it can maneuver adequately. (2) Several technical parameters of this Hexacopter, including the geometry, mass, the moment of inertia, until the estimation of motor throttle is required to achieve its hover conditions, both in the no-payload case and with-payload of 5 kg case. (3) The Hexacopter basic dynamic system model is based on the flight dynamics until its motion system control tuning through root locus map analysis using Simulink.